KONSORSIA BAKTERI PENGURAI SIANIDA YANG DI ISOLASI DARI BUANGAN INDUSTRI PENGOLAHAN EMAS - Sulistinah, Nunik; Sunarko, Bambang (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Bacterial consortium capable of growing and utilizing cyanide as a source of nitrogenÃ‚Â were isolated from effluent of gold mining industry. The isolation was conducted usingÃ‚Â liquid enrichment medium with potassium cyanide and glucose as nitrogen and carbonÃ‚Â source, respectively. These consortium could tolerate and were able to grow on KCN atÃ‚Â concentration of up to 1000 ppm. Bacterial consortium LP3 were also able to degradeÃ‚Â potassium cyanide and ammonium as product of the degradation. The degradation rateÃ‚Â was 9,0ÃŽÂ¼M per minute. The cyanide-degrading bacteria found in this consortium wereÃ‚Â identified as Bacillus, Corynebacterium, and Serratia.Keywords: potassium cyanide, nitrogen source, bacterial consortium LP3,degradation